Implementation of Hot Work Permits at PT Pertamina Geothermal Energy Karaha-Tasikmalaya Area - Andi Lala*; Samud Samud; Abdullah Abdullah (Universitas Syiah Kuala, 2024)
Labor is the main role involved in work activities in the company. Workers' activities are a source of work accidents. One effort to prevent work accidents in industry can be done through the implementation of a safe work permit system, including a hot work permit. A safe work permit system is a formal written system used to control work identified as potentially hazardous. The purpose of this study is to understand the program, procedures and implementation of hot work permits. This study was carried out using a qualitative descriptive method where data collection was carried out by field observation, interviews and literature study. This study was carried out at PT Pertamina Geothermal Energy Area Karaha which is located in Karaha Bodas Village, Kadipaten District, Tasikmalaya Regency, West Java. The results of this study are that the hot work permit program includes administrative checks such as JSA and Hot Work Permit; procedures and implementation refer to Government 50 of 2012 and Standard NFPA 51 B 2019. Based on the results of the study, work containing heat must attach a hot work permit, and socialization must be provided to workers in order to minimize the risk of accidents and fire.